'Stay home': age and gender frames and limits of residential family solidarities in the times of lockdown (a French example). (19th February 2021) - Kushtanina, Veronika; Vinel, Virginie
ABSTRACT: During the Covid-19 crisis, the residents of France were invited to stay at their homes. This representation of family as a shelter in case of difficulties has been prevailing within French family policies since the 1980s. In this paper, we question this integrating role family played during the lockdown through an on-line survey carried out during the shutdown. A sample of 4300 persons sheds light on the experience of this exceptional period. Four main results are presented in the article. Firstly, the residents of France of our sample tended to join their partner or family members. Secondly, the regrouping was gender-related: women were more often locked-downed with their relatives. Thirdly, this regrouping is linked to age – young people were more often welcomed in the households of their relatives than older adults or the elderly. And fourthly, the education level is also a relevant factor of family reunification for the lockdown.